Habilidades sociais e administração de tempo no manejo do estresse - de Sousa Pellegrini, Carla Fernanda [UNESP]; Calais, Sandra Leal [UNESP]; Salgado, Manoel Henrique [UNESP] (My University, 2012)
Recent searches suggest that social skills and time management as control variables of stress. In order to analyze possible relations between these variables and stress, it was done a descriptive study with a sample of convenience. Eighty three freshmen students, both of gender, of Biology, Civil Engineering and Psychology answered the Stress Inventory (ISSL), Social Skills Inventory (IHS) and a Time Management Inventory adaptation (ADT). It is emphasized that methodology of adaptation, the pro rata system, was not based on high standards of psychometry, which can lead to change of configuration of the instrument and the data it provides. The most of participants were unde rthe media in Social Skills and 72,29% manage badly the time. The stress rate was 48,19%. It was found connection between bad time management and stress and the lack of social skills was associated to bad time management. There wasn't statistic connection between stress and social skills lack. Students in Civil Engineering had the smaller stress rate, as well as the bigger lack of a Social Skills category.
Social skills and time management on stress handling
Keywords: College students; Social skills; Stress; Time management